2023
DOI: 10.1186/s10194-023-01577-2
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the aberrant brain functional connectivity in new daily persistent headache: a resting-state functional magnetic resonance imaging study

Abstract: Background and purpose The pathogenesis of new daily persistent headache (NDPH) is not fully understood. We aim to map aberrant functional connectivity (FC) in patients with NDPH using resting-state functional magnetic resonance imaging (MRI). Methods Brain structural and functional MRI data were acquired from 29 patients with NDPH and 37 well-matched healthy controls (HCs) in this cross-sectional study. Region of interest (ROI) based analysis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Forty HCs and 31 patients with NDPH were enrolled in the Headache Center, Department of Neurology, Beijing Tiantan Hospital, Capital Medical University from October 2020 to October 2022. This set of data was derived from previously published data 10 . Patients with NDPH were included if they met the following inclusion criteria: (1) Participants were included if they met the definition of NDPH as per the ICHD‐3 criteria 2 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Forty HCs and 31 patients with NDPH were enrolled in the Headache Center, Department of Neurology, Beijing Tiantan Hospital, Capital Medical University from October 2020 to October 2022. This set of data was derived from previously published data 10 . Patients with NDPH were included if they met the following inclusion criteria: (1) Participants were included if they met the definition of NDPH as per the ICHD‐3 criteria 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The sample size was based on the available data and previous literature. 10 We described normally distributed data as mean ± SD and non-normally distributed data as median with interquartile range. The chi-square test allowed comparison of gender between patients and HCs.…”
Section: Statistical Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…A study ( Qiu et al, 2023 ) using structural magnetic resonance imaging combined with multimodal brain imaging analysis of magnetoencephalography found that NDPH patients had abnormal brain morphology such as cortical area, cortical thickness, and gray matter volume, accompanied by abnormal cortical neural activity. Another study ( Wang et al, 2023 ) using fMRI to map abnormal FC in NDPH patients showed abnormal FC in multiple brain regions involved in emotion and pain perception and regulation, but these abnormalities did not correlate with clinical features. All in all, the exploration appears to be only superficial.…”
Section: The Role Of Fmri Technology In Diagnosing Primary Headachesmentioning
confidence: 99%